Building climate–security capacity across Africa - Taiwo, Ibukun (2025)
CGIAR and AGNES are strengthening climate–security capacity across Africa by embedding conflict-sensitive analysis into climate governance training. Through applied courses and tools, the partnership equips policymakers and practitioners to anticipate climate risks, reduce tensions, and design more resilient, peace-supporting climate actions.